2018
DOI: 10.1093/nar/gky023
|View full text |Cite
|
Sign up to set email alerts
|

The ribosomal A-site finger is crucial for binding and activation of the stringent factor RelA

Abstract: During amino acid starvation the Escherichia coli stringent response factor RelA recognizes deacylated tRNA in the ribosomal A-site. This interaction activates RelA-mediated synthesis of alarmone nucleotides pppGpp and ppGpp, collectively referred to as (p)ppGpp. These two alarmones are synthesized by addition of a pyrophosphate moiety to the 3′ position of the abundant cellular nucleotide GTP and less abundant nucleotide GDP, respectively. Using untagged native RelA we show that allosteric activation of RelA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 66 publications
6
73
1
Order By: Relevance
“…We propose that self-amplification of (p)ppGpp is required for spontaneous persister formation from a small input signal, such as gratuitous (p)ppGpp synthesis by YjbM or potentially RelA (Fig S7B). It was shown that RelA activity is also stimulated by pppGpp in E. coli (Kudrin et al, 2018). We hypothesize that this cooperativity may also contribute to spontaneous persister formation.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that self-amplification of (p)ppGpp is required for spontaneous persister formation from a small input signal, such as gratuitous (p)ppGpp synthesis by YjbM or potentially RelA (Fig S7B). It was shown that RelA activity is also stimulated by pppGpp in E. coli (Kudrin et al, 2018). We hypothesize that this cooperativity may also contribute to spontaneous persister formation.…”
Section: Discussionmentioning
confidence: 99%
“…The association of SpoT with the ribosome is still a matter of debate (11,12). In the case of RelA, the pppGpp product is a potent inducer of the enzyme’s synthesis activity (13). The mechanistic basis of this regulatory mechanism is currently unexplored, and it is unknown whether bifunctional RSHs Rel and SpoT are similarly regulated by pppGpp.…”
Section: Introductionmentioning
confidence: 99%
“…The former model suggests that upon activation by starved ribosomes RelA processively synthesises (p)ppGpp off the ribosome and the latter states that upon activation, RelA spends prolonged periods of time catalytically active in association with starved ribosomal complexes. Finally, there are two ‘flavours’ of the ‘short hopping time’ model: RelA could first bind the vacant A-site and then recruit the deacylated tRNA (13,14) or form the RelA:tRNA complex off the ribosome and deliver deacylated tRNA to the A-site, similarly to how elongation factor EF-Tu delivers aminoacylated tRNA (25,26). The proposed delivery of deacylated tRNA to the ribosome by RelA/Rel is a controversial topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that a C-terminal His 6 -tagged protein was used in that 434 study and RelA's C-terminus resides well inside the ribosomal complex, it was likely that the 435 functionality of the protein was compromised. In a recent report using untagged RelA 436 protein, it was shown that pppGpp as an allosteric regulator and GDP as substrate synergize 437 for the maximum enzymatic activity of RelA in vitro(Kudrin et al, 2018). Allosteric activation of Rel protein by pppGpp was not restricted to full-length RelA, it has also been 439 noted for RelQ, an RNA binding small alarmone synthase from Enterococcus faecalis 440(Beljantseva et al, 2017) and as well as the small alarmone synthase, SAS1, from Bacillus 441 subtilis(Steinchen et al, 2015).…”
mentioning
confidence: 99%